Deficiency of Human Adenosine Deaminase Type 2 – A Diagnostic Conundrum for the Hematologist - Pilania, Rakesh Kumar; Banday, Aaqib Zaffar; Sharma, Saniya; Kumrah, Rajni; Joshi, Vibhu; Loganathan, Sathish; Dhaliwal, Manpreet; Jindal, Ankur Kumar; Vignesh, Pandiarajan; Suri, Deepti; Rawat, Amit; Singh, Surjit (Frontiers in Immunology, 2022)
Deficiency of adenosine deaminase type 2 (DADA2) was first described in 2014 as a monogenic cause of polyartertitis nodosa (PAN), early onset lacunar stroke and livedo reticularis. The clinical phenotype of DADA2 is, however, very broad and may involve several organ systems. Apart from vasculitis, children may present with i) Hematological manifestations (ii) Lymphoproliferation and iii) Immunodeficiencies. Patients with DADA2 can have variable patterns of cytopenias and bone marrow failure syndromes. Patients with DADA2 who have predominant haematological manifestations are associated with ADA2 gene variants that result in minimal or no residual ADA2 activity. Lymphoproliferation in patients with DADA2 may range from benign lymphoid hyperplasia to lymphoreticular malignancies. Patients may present with generalized lymphadenopathy, splenomegaly, autoimmune lymphoproliferative syndrome (ALPS) like phenotype, Hodgkin lymphoma, T-cell large granular lymphocytic infiltration of bone marrow and multicentric Castleman disease. Immunodeficiencies associated with DADA are usually mild. Affected patients have variable hypogammaglobulinemia, decrease in B cells, low natural killer cells, common variable immunodeficiency and rarely T cell immunodeficiency. To conclude, DADA2 has an extremely variable phenotype and needs to be considered as a differential diagnosis in diverse clinical conditions. In this review, we describe the evolving clinical phenotypes of DADA2 with a special focus on haematological and immunological manifestations.